Knowledge, Attitude, and Practice Among Nurses Regarding Nutrition Management of Diabetes Mellitus Patients - Imam Tri Sutrisno; Rafika Rosyda; Nandar Wirawan; Sandi Alfa Wiga Arsa (Journal of Ners and Midwifery, 2024)
Diabetes mellitus is a chronic metabolic disorder that contributes significantly to the global health burden, with a rising prevalence globally. Understanding nurses' knowledge, attitudes, and practices (KAP) is crucial because knowledge provides essential insights into how diet affects blood glucose levels, a positive attitude encourages support for patient adherence, and efficient practices ensure the consistent application of dietary management strategies. This study aimed to assess the KAP among nurses about the nutritional management of Diabetes. This descriptive study involved 100 nurses working in medical and surgical wards of a hospital, with 99 respondents included in the analysis following the dropping out of one respondent. Data was collected using a structured questionnaire designed to evaluate the KAP of nurses concerning diabetes nutritional management. The study found disparities in the levels of knowledge among nurses: 14.1% demonstrated high knowledge, 49.5% demonstrated intermediate knowledge, and 36.4% demonstrated poor knowledge. Despite these variations, none demonstrated a bad attitude, a lousy 11.1% demonstrated an intermediate attitude, and the majority of nurses (88.9%) exhibited high attitudes towards Diabetes nutritional management. Additionally, 0% engaged in harmful practices, 4% demonstrated intermediate practices, and nearly all respondents (96%) reported engaging in good practices. These results underscore the need for targeted educational interventions to bridge knowledge gaps. Enhancing nurses' knowledge in Diabetes nutritional management is essential to improve the quality of care and health outcomes for patients with Diabetes.